Screening of onion cultivars for resistance against Thrips tabaci in relation to weather conditions - Moraiet, Maher Ahmed; Ansari, M Shafiq; Ahmad, Salman (Indian Journal of Plant Protection, 2020)
Cultivars of onion i.e. White Marglobe, Onion White, Nasik Red, Tanzanian Red, Nasik Red Plus N-53, Onion Kessar, Onion-Indam Marshal-(Synth-3) and Onion Dr-301 (Krishna) were screened for resistance against onion thrips, Thrips tabaci in relation to weather conditions for two consecutive years (2011/12-2012/13). Weekly observations were made on the density of thrips per plant two weeks from the day after transplanting (DAT) up to harvesting and yield was recorded after 112 DAT. Initial infestation started from 3rd week of February at 56 DAT and increased gradually up to harvesting in both years. Generally, density of thrips did not differ significantly (P=0.05) on cultivars, but a significant (P=0.05) difference was observed between cultivars and their yields. Yield was significantly higher in White Marglobe followed by Onion Dr-301 (Krishna) and lowest in Onion White. White Marglobe harbored less thrips with higher yield than other cultivars. Temperature and relative humidity were the most important weather factors affecting thrips population on onion than other weather factors. Generally, a significantly (P=0.05) positive correlation was found between temperature and the density of thrips on cultivars. Average relative humidity was correlated negatively significant (P=0.05) in relation to the density of thrips on all cultivars.